2007
DOI: 10.1002/bsl.791
|View full text |Cite
|
Sign up to set email alerts
|

Death qualification and prejudice: the effect of implicit racism, sexism, and homophobia on capital defendants' right to due process

Abstract: Two hundred venirepersons from the 12th Judicial Circuit in Bradenton, Florida completed the following measures: (1) one question that measured their level of support for the death penalty; (2) one question that categorized their death-qualification status; (3) 23 questions that measured their attitudes toward the death penalty (ATDP); (4) 22 questions that assessed their attitudes toward women (ATW); (5) 25 questions that measured their level of homophobia (H); (6) seven questions that assessed their level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Some research has indicted that European Americans' racial prej udice is linked to favorable death penalty attitudes (Butler, 2007;Young, 2004), but little is known regarding how racial prejudice would interact with mitigating factors to predict juror bias in death penalty cases.…”
Section: Strength Of Mitigating and Aggravating Circumstancesmentioning
confidence: 99%
“…Some research has indicted that European Americans' racial prej udice is linked to favorable death penalty attitudes (Butler, 2007;Young, 2004), but little is known regarding how racial prejudice would interact with mitigating factors to predict juror bias in death penalty cases.…”
Section: Strength Of Mitigating and Aggravating Circumstancesmentioning
confidence: 99%
“…When the research is about finding liability and then making an award we feel this is conceptually more similar to the two-step hurdle model. In research on capital cases, the zero-inflated models may be more appropriate because there are people who are unwilling to murder someone under any circumstance (and these people are often excluded from both stages of the judicial process, creating biases, Butler, 2007). Of course, many judicial processes require jurors go through more than two steps.…”
Section: Summary: Awards After Verdictmentioning
confidence: 99%
“…The zero‐inflated models might be better suited for capital trial decision making. There may be two distinct classes of people: those unwilling ever to murder somebody (i.e., to vote for execution) and those willing to murder another person during certain situations (Butler, 2007; Kadane, 1983).…”
Section: Amount Awarded After Verdictmentioning
confidence: 99%
“…This is particularly troubling when considered in context with studies on death qualification and prejudice. A recent study found that death‐qualified individuals showed more prejudice in terms of homophobia, modern racism, and modern sexism (Butler, 2007a). If death qualification more often excludes minorities and women, and includes individuals who are more likely to be prejudiced against minorities and women, this could seriously impact the due‐process rights of the defendant.…”
Section: Demographicsmentioning
confidence: 99%